Fulfillment of Basic Psychological Needs Through Eudaimonic Activities on Subjective Well-Being of Islamic Elementary School Children - Tazkiyah, Fairuz; Abidin, Fitri Ariyanti (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2024)
This research further examines and analyzes the fulfillment of the basic psychological needs of subjective wellbeing of Madrasah Ibtidaiyah children through Eudaimonic Activities. The mixed methods design used in this research provides a strong framework for capturing the diverse nature of children's experiences with eudaimonic activities. This research was carried out at Jatinagor Elementary School. The population is fifth-grade students at Jatinagor Elementary School. The sampling technique used in data collection is convenience sampling. Participants in this study were pre-adolescent students aged 11 to 12 years. The number of participants in this study was 81 children. Data analysis was carried out by calculating the overall score obtained from the BPNFS and SPANE measuring instruments and then averaging them. The interesting finding was that playing online games was a common form of entertainment among the participants. This suggests that digital play can be an important aspect of children's lives, potentially contributing to their eudaimonic wellbeing if managed appropriately. These insights pave the way for further research into how online games can be integrated into educational environments in ways that support children's developmental needs. Additionally, the results of this study provide concrete examples of eudaimonic activities, which can be invaluable for educators and parents who wish to understand and develop children's innate potential.